â€œCherchons la femme!â€: The Dynamics of Gender Relations and Emergent Complexity in Neolithic Ã‡atalhÃ¶yÃ¼k - Dederen, Jean-Marie; Mokakabye, Jennifer (Journal for Semitics, 2018)
Ever since the first artefacts and structures of Çatalhöyük were excavated by James Mellaart in the 1960s, researchers have debated why sedentary farmers, whose diet included domesticated plants, sheep and goat, displayed a myriad of aurochs bull and other hunting trophies inside some of their houses. Equally puzzling have been two parallel developments in the later habitation levels. On the one hand the excavators noted how the wild animal trophies gradually decreased in number and eventually faded away towards the final Neolithic occupation. On the other hand they established that the material and symbolic presence of women in this prehistoric town was growing stronger. It is proposed that these two processes were connected and that they can be elucidated in terms of the female–male dialectic which may have generated them.